Monitoring of nanoparticle reactivity in solution: interaction of l-lysine and Ru nanoparticles probed by chemical shift perturbation parallels regioselective H/D exchange. Issue 43 (15th May 2017) - Martínez-Prieto, Luis M.; Baquero, Edwin A.; Pieters, Grégory; Flores, Juan C.; de Jesús, Ernesto; Nayral, Céline; Delpech, Fabien; van Leeuwen, Piet W. N. M.; Lippens, Guy; Chaudret, Bruno
Abstract : The regioselective H/D exchange ofl -lysine at different pHs can be correlated with the coordination modes of the lysine ions to the Ru surface as found by NMR. Abstract : Thanks to new water-soluble Ru nanoparticles (NPs) stabilized by sulfonated NHC ligands, we demonstrate that it is possible to monitor the catalyst/substrate interaction using NMR chemical shift perturbations (CSPs), under conditions that closely resemble those applied during the enantiospecific C–H deuteration ofl -lysine. Correlating the pH dependence of the interaction ofl -lysine with the surface of the RuNPs and its subsequent deuteration, our study underscores the importance of oriented binding to the surface as a critical factor for H/D exchange.